Review Of the Effectiveness of The Central Java Province Government's Cooperative and Sme Development Program - Widyastuti, Ariyani; Avi Budi Setiawan; Adriani Dimasari (Efficient: Indonesian Journal of Development Economics, 2024)
In order to improve the achievement of development of the Cooperative and MSME sectors and to find out the extent of the effectiveness of the programs/activities that have been carried out towards achieving targets in accordance with the organization's vision and mission, it is necessary to conduct an evaluation of the program or activity and its recommendations. Through this evaluation activity, the weaknesses or obstacles faced will be identified, so that the results can be used as information to make corrections or improvements to the implementation of the program in the future. The purpose of this study is to conduct evaluations and provide recommendations for various programs in the strategic plan that have been implemented by the cooperative and UMKM service in Central Java. The quantitative approach aims to provide recommendations for the cooperative and UMKM development program of the Central Java provincial government using the ANP (Analytic Network Process) method. This study uses Logical Framework analysis to determine the evaluation of the cooperative and UMKM development program of the Central Java provincial government.